2019
DOI: 10.1016/j.echo.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Holographic Display for Quantification of Mitral Annular Dynamics by Three-Dimensional Echocardiography

Abstract: Background: Three-dimensional (3D) echocardiography with multiplanar reconstruction (MPR) is used clinically to quantify the mitral annulus. MPR images are, however, presented on a two-dimensional screen, calling into question their accuracy. An alternative to MPR is an autostereoscopic holographic display that enables indepth visualization of 3D echocardiographic data without the need for special glasses. The aim of this study was to validate an autostereoscopic display using sonomicrometry as a gold standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The non-planar saddle shape of the MA helps to maintain normal valve function by decreasing the blood ow pressure on the valves. [15,16] In a previous study, it was reported that NPA is better than AH/ALPMD at re ecting the attening of the MA because it is independent of changes in pre-and afterload heart. [15] In addition, the nadir point of AH is the midpoint of the mitral posterior annulus, and the nadir point of NPA is the midpoint of the ALPMD; which means these two parameters are not uniform, and there is only a weak correlation between NPA and AH/ALPMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-planar saddle shape of the MA helps to maintain normal valve function by decreasing the blood ow pressure on the valves. [15,16] In a previous study, it was reported that NPA is better than AH/ALPMD at re ecting the attening of the MA because it is independent of changes in pre-and afterload heart. [15] In addition, the nadir point of AH is the midpoint of the mitral posterior annulus, and the nadir point of NPA is the midpoint of the ALPMD; which means these two parameters are not uniform, and there is only a weak correlation between NPA and AH/ALPMD.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] In a previous study, it was reported that NPA is better than AH/ALPMD at re ecting the attening of the MA because it is independent of changes in pre-and afterload heart. [15] In addition, the nadir point of AH is the midpoint of the mitral posterior annulus, and the nadir point of NPA is the midpoint of the ALPMD; which means these two parameters are not uniform, and there is only a weak correlation between NPA and AH/ALPMD. In our study, the increased NPA con rmed that the MA was attened in AF patients with LV dysfunction and in those without LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%